Improved optoelectronic properties of Yttrium co-doped CdO:Zn thin films fabricated by nebulizer spray pyrolysis method for TCO applications. (25th November 2021) - Sarath Babu, R; Murthy, Y Narasimha; Loyola Poul Raj, I; Revathy, M S; Chidhambaram, N; Ganesh, V; Algarni, H; Yahia, I S
Abstract: To understand the effect of Yttrium (Y) co-doping with CdO:Zn towards optoelectronics applications, the thin films were coated by the nebulizer spray pyrolysis route. The microstructural studies (XRD) reveals that the crystallite size decreases from 20 to 15 nm with the increase of Y concentrations. The surface topography of the films has been strongly influenced by the Y doping which is evident from the AFM images. The presence of Cd, O, Zn, and Y has been confirmed through the EDX spectrum. The transparency is higher (81%) for the CdO:Zn-Y(1.5%) film. The decreasing trend in the values of the optical dielectric constant is observed with increases in yttrium content. The enhancement in the carrier concentration (12 × 10 20 cm −3 ) and reduction in the electrical resistivity (8.4 × 10 −4 Ωcm) have been observed for the CdO:Zn-Y(1.5%) film via the Hall-effect measurements. In addition, the heterojunction p-Si/n-CdO:Zn-Y(1.5%) photodiode was fabricated to understand the optical sensing properties. The current values of the fabricated photodiode are found to enhance as the intensity of the illumination increases from1.0 to 3.0 mW cm −2 . Moreover, the photodiode exhibits the highest responsivity, detectivity, and external quantum efficiency value of 1.45 AW −1, 6 × 10 9 Jones, and 339%, respectively with excellent switching speeds. This work provided a guideline to develop a TCO layer and photodiode towards the applications of optoelectronic-based devices.